Intraday Speed of Adjustment and Realized Variances in the Indonesia Stock Exchange - Husodo, Zäafri Ananto; Henker, Thomas (The Indonesian Capital Market Review, 2009)
We examine the intraday trading and price dynamics for frequently traded stocks at the Indonesian Stock Exchange. Using trade price, time series generated at one, two, three, five, ten, fifteen, thirty and sixty-minute intervals, we estimate the speed of adjustment and the corresponding realized variance of these series. The objective of the estimation is to infer the noise impact to the deviation of observed prices from their fundamental value. The result from the speed of adjustment estimate is consistent with the realized variance estimator. Both conclude that the 50 most frequently traded stocks in the Indonesia Stock Exchange adjust to new information within 30 minutes. At the interval, the coefficient of the speed of price adjustment is insignificantly different from zero implying negligible noise impact to the observed price. Concurrently, the realized variance starts to stabilize at 30-minute interval purporting fading impact of noise to the realized variance estimate. The evidence justifies the use of realized variance at various intervals as a reliable indicator of price discovery rate in the Indonesia Stock Exchange